Sociodemographical and clinical presentation of traumatic brain injury patients - Mondol, Muhammed Alamgir; Rahman, Nadia; Akhter, Shohela; Ahmed, Badrunnesa; Rahman, Azizur; Momen, Md Abdul; Rahman, Mahmudur; Talukder, Debesh Chandra (Journal of Dhaka Medical College, 2013)
Background: Traumatic brain injury (TBI) is a non degenerative, non congenital insult to the brain from an external force, possibly leading to permanent or temporary impairment of cognitive, physical and psychosocial functions with association of diminished and altered state of consciousness. It accounts for approximately 40% of all deaths from acute injuries in the united state. Twenty percent of TBI occurs in the paediatric age young people and men aged about 15-30 are the high risk of population. The study is to define TBI appropriately, to know the causes of TBI, clinical presentations and severity of TBI patients in our hospital. Methods: A direct observational study was carried out from 18th July, 2010 to 31st December, 2010. Total numbers of patients were 100. A semi structured pretest questionnaire was used to take proper history, clinical assessment, their management and programs. Results: A total of 100 patients with traumatic brain injury (TBI) in which 84% were male and 16% were female. Out of 100 patients irrespective of sex it was observed that most patients that is 26% belongs to age group 26-35yrs then 24% belongs to age group 16-25yrs. Out of 100 patients 48% was RTA (Road traffic accident) then 28% was assault and 22% belongs to fall in. Out of 100 patients it was observed that most presenting complaints was unconscious 42%, headache 36% and vomiting 26%, mental functions i.e. unconscious 42% and 36% belongs to normal. 42% showed impaired motor and 20% sensory. 62% complaint unable to walk. Bladder dysfunction belongs to 64%. Conclusion: Traumatic brain injury accounts 40% of all death from acute injuries in the developed country. This percentage is now increasing in developing country like Bangladesh. So government and private organizations should setup more trauma centre and can enhance to decrease the adverse conditions. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15623 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 45-50